A Weighted-Based Approach To Prioritize User Preferences In Information Retrieval - Al-Qudah, Mashal Kasem (2008)
Tourism statistics point towards increased tourist or citizen mobility in holiday destinations, with a subsequent rise in associated externalities, above all those related with the use of hire cars. Currently, there are a large number of car rental companies operating through the internet. They offer various services relating to vehicle hiring, nevertheless, these online business are not organize into a single retrieval system. Information retrieval (IR) is the art of searching for text, for information within text and for metadata about text, as well as that of searching the World Wide Web and relational databases. Information systems including the internet uses hypertext format. The critical idea carried out by a weighted based algorithm is that, when one attributes links to another, it is basically casting a vote for the other attribute. The higher the number of votes that are cast for an attribute, the higher the significance of the attribute. In order for customer to get a good bargain, he has to personally visit the car rental companies or their relevant websites and later manually perform the required comparison. Furthermore, the existing online car rental services do not include users' preferences in a rental booking. The objective of this work is two-fold; to combine information on car rental services from three companies into a single system and to use a weighting scheme to prioritize a customer's preferences on the car to be hired. The proposed approach is intended to help customers to hire the required car from the company that offers the best services. Based on the result presented in the earlier subsections, we concluded that the respondents felt version B is better than version A. This shows that by applying a weighted-based approach, relevancy of the retrieved results is improved and at the same time fulfilled user preferences.